2013
DOI: 10.4236/aces.2013.34027
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Bubbles with Vortex Ring Launched into Bubble Plume

Abstract: This study is concerned with an experimental exploration for the interactions of bubbles with a vortex ring launched vertically upward into a bubble plume. A vortex ring launcher, composed of a cylinder and a piston, is mounted at the bottom of a water tank. Small hydrogen bubbles are released into still water from a cathode, which is wound around the cylinder outlet, by the electrolysis of water. The bubbles rise by the buoyant force and induce a bubble plume. The water in the cylinder is discharged into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 25 publications
5
23
0
Order By: Relevance
“…There have also been studies of the interaction of vortex rings with a large number of microbubbles. These include the experimental study of Uchiyama & Kusamichi (2013), and the simulations of Ferrante & Elghobashi (2007). In the latter case, involving the interactions of a large number of microbubbles with a Taylor-Green vortex, Ferrante & Elghobashi (2007) observed that bubbles settle in the core of the vortex, reducing the vorticity and enstrophy.…”
Section: Literature Overviewmentioning
confidence: 99%
“…There have also been studies of the interaction of vortex rings with a large number of microbubbles. These include the experimental study of Uchiyama & Kusamichi (2013), and the simulations of Ferrante & Elghobashi (2007). In the latter case, involving the interactions of a large number of microbubbles with a Taylor-Green vortex, Ferrante & Elghobashi (2007) observed that bubbles settle in the core of the vortex, reducing the vorticity and enstrophy.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Small gas bubbles in a liquid flow preferentially distribute around the high-vorticity region [8,9]. By noting that the vorticity is highly concentrated on the vortex core of the vortex ring, one of the authors [10] conducted an experimental study on the behavior of a vortex ring in bubbly mixtures. Small hydrogen bubbles were generated by water electrolysis at the bottom of a water tank.…”
Section: Introductionmentioning
confidence: 99%
“…The present authors [1]- [3] have performed numerical and experimental investigations on the transport of bubbles in water. Uchiyama [1] conducted a numerical simulation of a water jet laden with small air bubbles and showed that a vortex ring, induced near the nozzle outlet by an axisymmetric disturbance, incorporates the bubbles and convects with them along the jet centerline.…”
Section: Introductionmentioning
confidence: 99%
“…Their simulation found that the bubbles are entrained and transported by the vortex ring and that the strength of the vortex ring is affected by the entrained bubbles. Uchiyama and Kusamichi [3] performed an experimental study to explore the interaction between a bubble cluster and a vortex ring. Small hydrogen bubbles were generated by water Manuscript received March 16, 2017; revised July 5, 2017.…”
Section: Introductionmentioning
confidence: 99%